Platinum(II) complexes containing pyridyl-substituted thiourea dianion and monoanion ligands: Synthesis, structural chemistry, and theoretical investigations - Okpareke, Obinna C.; Lane, Joseph R.; Tiekink, Edward R. T. *; Henderson, William (Elsevier, 2023)
Reactions of cis-[PtCl2(PPh3)2] with the 2-pyridyl-substituted thioureas py(CH2)nNHC(S)NHC6H4R (R = H, OMe or NO2; n = 0, 1 or 2) in methanol with Et3N base, followed by precipitation with water gave good yields of the complexes [Pt{SC(NC6H4R)(N(CH2)npy)}(PPh3)2]. The compounds were characterised 1H NMR, 31P{1H} NMR, FTIR and single crystal X-ray crystallography. The initial NMR investigation indicated the possibility of isomerism in the complexes. 31P{1H} NMR investigations revealed the presence of an initial distal isomer for the dianion complexes, which underwent solution phase isomerization into the proximal isomeric forms of the complexes and/or a mixture of the proximal and distal isomers. The opposite trend was recorded for the monoanionic complex with the formation of an initial proximal isomer and subsequent isomerisation into 1:3 mixture of the distal and proximal isomeric forms of the complex. The degree of isomerization was observed to be related to the difference in energy between the two isomeric forms of the complex and the nature and size of the R substituents in the complex. The molecular geometries of a number of the compounds showed a distorted square-planar geometry defined by a NP2S donor set. The thiourea ligand acts as (N,S)-chelating dianionic ligand so that each donor atom is opposite a phosphane-P atom; a trans-influence is evident on the Pt-P bonds. In each complex, the pyridyl-substituted nitrogen is coordinated to platinum. The cationic complex [Pt{SC(NPh)(NHCH2py)}(PPh3)2]+ was also isolated as its BF4- salt by addition of excess NaBF4 to the reaction mixture. In this complex, the thiourea monoanion coordinates in a distal manner, with the NHCH2py group remote from the platinum centre. Charge-assisted ammonium-Nsingle bondH…N(pyridyl) bonding leads to dimeric aggregates. These, along with the neutral molecules [Pt{SC(Np-C6H4R2)(N(CH2)npy)}(PPh3)2] are assembled into the three-dimensional crystal via weak non-covalent interactions. Characterisation by 31P{1H} NMR spectroscopy showed the presence of several isomeric species in solution.